2009
DOI: 10.1037/a0015519
|View full text |Cite
|
Sign up to set email alerts
|

Reducing sexual risk behaviors and alcohol use among HIV-positive men who have sex with men: A randomized clinical trial.

Abstract: This randomized clinical trial (N = 253) evaluated the efficacy of a theory-based intervention designed to reduce both alcohol use and incidence of unprotected sexual behaviors among HIV-positive men who have sex with men with alcohol use disorders. An integrated, manualized intervention, using both individual counseling and peer group education/support, was compared with a control condition in which participants received resource referrals. The intervention was based on the transtheoretical model’s stages and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
155
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(156 citation statements)
references
References 59 publications
1
155
0
Order By: Relevance
“…Implicit in MI, as in most psychosocial models of behavior change, is the assumption that risk behaviors are largely under the control of the individual (Fisher & Fisher, 2000), and the intervention therefore risks failing to address the full range of factors that influences MSM's sexual behaviors, such as the strong interpersonal and social forces (see, e.g., Berg, 2008;Muñoz-Laboy & Dodge, 2007;Tieu et al, 2011). Among the three included studies in this systematic review that assessed the effectiveness of MI on both AOD use and sexual risk behaviors, two found an effect for AOD use but not sexual risk behaviors (Morgenstern et al, 2007;Velasquez et al, 2009), and the third found no effect for either outcome type (Morgenstern et al, 2009). Also previous efforts to reduce sexual risk behaviors using MI have yielded mixed results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Implicit in MI, as in most psychosocial models of behavior change, is the assumption that risk behaviors are largely under the control of the individual (Fisher & Fisher, 2000), and the intervention therefore risks failing to address the full range of factors that influences MSM's sexual behaviors, such as the strong interpersonal and social forces (see, e.g., Berg, 2008;Muñoz-Laboy & Dodge, 2007;Tieu et al, 2011). Among the three included studies in this systematic review that assessed the effectiveness of MI on both AOD use and sexual risk behaviors, two found an effect for AOD use but not sexual risk behaviors (Morgenstern et al, 2007;Velasquez et al, 2009), and the third found no effect for either outcome type (Morgenstern et al, 2009). Also previous efforts to reduce sexual risk behaviors using MI have yielded mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…Further, lack of provider MI training is an unlikely explanation of the limited effectiveness demonstrated. Across the 10 studies, therapists providing MI had received extensive MI training; several included training by MINT members (e.g., Picciano et al, 2001;Velasquez et al, 2009). A recent systematic review by Lundahl and colleagues (2010) found that level of MI training did not influence the success of MI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Past behavioral interventions among HIV-positive MSM have targeted sexual risk (Coleman et al, 2009;Kalichman et al, 2001;McKirnan et al, 2010;Serovich et al, 2009;Simon Rosser et al, 2010;Williams et al, 2008) or sexual risk and drug use (Fisher et al, 2006;Lapinski et al, 2009;Mausbach et al, 2007;Rotheram-Borus et al, 2004;Velasquez et al, 2009;Wong et al, 2008). Many of these interventions have shown at least modest success in achieving their intended outcomes.…”
Section: H IV Continues To Disproportionately Affect Men Who Have Sexmentioning
confidence: 99%